Physiological screening for drought tolerance in Mediterranean long-storage tomato. (August 2016) - Patanè, Cristina; Scordia, Danilo; Testa, Giorgio; Cosentino, Salvatore L.
Highlights: Plant physiology of ten long-storage tomatoes was studied under no irrigation. Positive relationship of leaf transpiration vs . relative water content was observed. Inverse relationship of relative water content vs . proline was described. Productivity during water stress was not correlated to increases in tissue proline content. Leaf transpiration was the most reliable indicator for yield prediction. Abstract: Long-storage tomato is a drought-tolerant plant traditionally cultivated under no water supply in semi-arid areas of Italy. In 2009, physiological traits of ten "long-storage" tomato lines cultivated under no irrigation were screened for low soil water tolerance. Leaf relative water content (RWC), proline content and leaf transpiration ( E ) were measured throughout the growing season. Instantaneous leaf water use efficiency was also calculated on a single date, as the ratio between net photosynthesis ( A ) and E . Close relationships were observed among the physiological parameters, positive for E vs . RWC and inverse for RWC and E vs . proline. Results indicate that the increase in proline concentration involves a water stress tolerance, and genotypes more sensitive to soil water deficit respond to drought stress through less proline in leaves. Close significant linear relationships (positive with RWC and E, negative with proline) were also found between fruit yield and all the physiological parameters examined. Among them, the most reliable indicator for yield prediction under water restriction was leaf transpiration rate as measured at the flowering stage. The study made it possible to understand the complex relationships between physiological processes, drought tolerance, and plant productivity in long-storage tomato, and to identify those traits that regulate plant physiology under low water availability.